Seasonal changes in the gonadal state of the oysters Crassostrea iridescens and Crassostrea corteziensis (Filibranchia: Ostreidae) in the Northwest coast of México. - Frías-Espericueta, Martín G. (1997)
The reproductive cycle in oysters has been the subject of several studies in temperate zones. However, little information is available for tropical and subtropical species. This study describes the seasonal changes in the gonadic index (GI) of two species of oysters, Crassostrea iridescens and Crassostrea corteziensis, which differ markedly in their hàbitad and time of reproduction. Both oysters were sampled at 45 days intervals in the Northwest coast of Mexico between November 1989 and October 1990. Gonadal and somatic tissue per individual were dried for three days at 90°C, weighed and recorded. The gonadic index (GI) applied in this work was calculated from: GI = Wg/ws. Were WG is the average gonadal tissue dry weight, and Ws is the average somatic tissue dry weight. Seasonal variations in the gonadal state were evident for the two species. C.iridescens exhibited only a single maximum in the year, while C. corteziensis two peaks. This situation is presumably related to the contrastable environmental conditions that prevail in the sites where each species inhabit.